2004
DOI: 10.1177/014556130408300118
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Skin Endpoint Titration and Skin-Prick Testing in the Diagnosis of Allergic Rhinitis

Abstract: A bstract Among the many methods ofallergy diagnosis are intradermal testing (/DT) and skin-prick testing (SPT). The usefulness of /DT has been called into question by some authors, while others believe that studies demonstrating that SPT was superior might have been subje ct to bias. We conducted a study to compare the validity ofSPT and IDT-specifically, the skin endpoint titration (SET) type of /DT-in diagnosing allergic rhinitis. We performed nasal provocation testing on 62 pati ents to establish an unbias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…If ID testing is negative after a negative SPT, it is concluded that the patient is unlikely to be sensitive to that allergen . However, if ID testing is positive after a negative SPT, it is possible that this indicates clinically relevant allergy …”
mentioning
confidence: 99%
“…If ID testing is negative after a negative SPT, it is concluded that the patient is unlikely to be sensitive to that allergen . However, if ID testing is positive after a negative SPT, it is possible that this indicates clinically relevant allergy …”
mentioning
confidence: 99%
“…A recent study showed that IDT compared favorably with both SPT and nasal provocation testing (NPT). In fact, there was no statistically significant difference in the positive or negative predictive value between IDT and SPT 37 . This paper is especially significant because it uses a third technique, NPT, as a means to compare IDT and SPT.…”
Section: Introductionmentioning
confidence: 91%
“…In fact, there was no statistically significant difference in the positive or negative predictive value between IDT and SPT. 37 This paper is especially significant because it uses a third technique, NPT, as a means to compare IDT and SPT. One of the limitations of this study was the sample size (n ϭ 62), but the study was powered to be able to show equivalency between the testing techniques.…”
Section: Allergy Skin Testing: History and Current Controversymentioning
confidence: 99%
“…Diagnostic approaches in ragweed-induced allergic rhinitis include obtaining the patient’s precise medical history, especially in terms of potential sources of exposure, seasonal symptoms of nasal inflammation, and relevant comorbidities like asthma. Following this, a skin prick test 38 and nasal provocation are the main clinical tests applied today. In vitro testing allows for the subclassification of allergens and cross-reactions.…”
Section: Specifics Of Ragweed-induced Rhinoconjunctivitismentioning
confidence: 99%